Experimental investigation and optimization of lightweight concrete bricks developed using vermiculite - Ganasen, Nakkeeran; Bahrami, Alireza; Loganathan, Krishnaraj (Frontiers in Materials, 2023)
Concrete production requires a wealth of resources, including cement, aggregate, and water. Therefore, in terms of maintaining the earth's natural ecosystems and resources, researchers need to find sustainable and green methods for producing concrete. The focus of the current research is the use of potentially harmful alternative aggregates to manufacture lightweight concrete bricks. In this study, cement, fine aggregates, and vermiculite are the concrete brick mix components. Three trail mixes are followed by a replacement ratio of 60:40, 50:50, and 40:60 for fine aggregates in brick. Statistical techniques are exerted to compare all the experimental results. Initially, regression analysis was employed to determine the precise relationship between the dependent and independent variables of the study. Furthermore, the compressive strength of concrete brick was investigated. As a result of the research, vermiculite concrete bricks with compressive strengths ranging from 3.2 to 5.9 N/mm2 and densities ranging from 1780 to 2142 kg/m3 were obtained. The regression model captured the variability of the data as evidenced by the suitable R2 threshold (R2 > 0.9935). Subsequently, every property of the concrete bricks was predicted using Regression, Surface plots, Main plots, and Heatmap. The conclusion of the study demonstrated that the models generated very effective results.